2016
DOI: 10.1021/acsnano.6b03496
|View full text |Cite
|
Sign up to set email alerts
|

Highly Tunable Colloidal Perovskite Nanoplatelets through Variable Cation, Metal, and Halide Composition

Abstract: Colloidal perovskite nanoplatelets are a promising class of semiconductor nanomaterials-exhibiting bright luminescence, tunable and spectrally narrow absorption and emission features, strongly confined excitonic states, and facile colloidal synthesis. Here, we demonstrate the high degree of spectral tunability achievable through variation of the cation, metal, and halide composition as well as nanoplatelet thickness. We synthesize nanoplatelets of the form L2[ABX3]n-1BX4, where L is an organic ligand (octylamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
774
6
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 523 publications
(826 citation statements)
references
References 58 publications
34
774
6
12
Order By: Relevance
“…We and others have shown that the thickness of individual nanoplatelets can be determined by AFM (Figure 3b), however this becomes impossible in the case that the nanoplatelets form stacks. [9,11,22,27] In x-ray scattering experiments, the stacking of nanoplatelets gives rise to a new series of Bragg peaks, enabling the [15] Copyright 2016, American Chemical Society. b) AFM image of colloidal CsPbBr 3 nanoplatelets; scale bar: 1 µm.…”
Section: Characterization Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We and others have shown that the thickness of individual nanoplatelets can be determined by AFM (Figure 3b), however this becomes impossible in the case that the nanoplatelets form stacks. [9,11,22,27] In x-ray scattering experiments, the stacking of nanoplatelets gives rise to a new series of Bragg peaks, enabling the [15] Copyright 2016, American Chemical Society. b) AFM image of colloidal CsPbBr 3 nanoplatelets; scale bar: 1 µm.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…[9,15] However, the type of monovalent cation can greatly influence the stability and PLQY of perovskite nanocrystals. [15] It has been found that all-inorganic perovskite nanocrystals, which generally contain Cs + as the A-site cation, replacing the MA + , and are fabricated using the hot-injection method, exhibit higher stability as well as higher PLQYs than organic/inorganic hybrid perovskites. [3,10,32] The groups of Manna and Alivisatos extended this approach to 2D nanocrystals, simultaneously reporting CsPbX 3 nanoplatelets.…”
Section: Ligand-guided Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…12,16,17 The size and shape of the particles are important factors determining the resulting optical properties because of their influence on the bandgap, known as the quantum size effect. 18,19 CsPbX 3 nanocrystals are frequently synthesized in the form of nanocubes, while two-dimensional morphologies such as nanosheets and nanoplatelets are also obtained. Pan et al reported the dependence of the particle morphology on the synthesis temperature and the length of the n-alkyl carboxylic acids and n-alkylamines used in the hot-injection method, as summarized in Figure 5.…”
Section: Influence Of Organic Ligands On Particle Morphologies Of Cspmentioning
confidence: 99%